Influence of ShuJinHuoXue Tablets on Ischemia Reperfusion Injury of Animals’ Skeletal Muscle - Fang Yu; Zhonghua Liu; Haidong Liang; Zhihong Tong (Molecules, 2012)
Ischemia-reperfusion (IR) can lead to serious tissue oxidative injury in animals. ShuJinHuoXue tablet (SJHXT) is a Chinese Traditional Medicine which can relax the muscles and stimulate the blood circulation and has been used as a clinical medicine. In the present study, we investigated the effects of SJHXT pretreatment on oxidative injury using an animal model of acute limb IR. Results showed that SJHXT pre-treatment (200, 300 and 400 mg/kg/day) markedly reduced serum endothelin-1 (ET-1), thromboxane B2 (TXB2) levels and thromboxane B2/6-keto- prostaglandin F1α (TXB2/6-Keto-PGF1α), wet weight/dried weight (W/D) ratio, myeloperoxidase (MPO), creatine kinase (CK), lactate dehydrogenase (LDH) activities, and increased serum nitric oxide (NO), 6-Keto-PGF1α levels and NO/ET-1 ratio in the IR+SJHXT groups. In addition, the SJHXT pre-treatment (200, 300 and 400 mg/kg/day) markedly reduced skeletal muscle Ca2+, malondialdehyde (MDA) levels, increased Na+-K+-ATPase, Ca2+-Mg2+-ATPase, superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) activities. Our results suggest that SJHXT pre-treatment may improve skeletal muscle blood vessel microcirculation, decrease skeletal muscle oxidative injury and enhance antioxidant enzymes activities in IR animals.